Clinical-pathological characterisation of children with B-cell non-Hodgkin lymphoma over a ten year period at a tertiary centre in Cape Town - Kriel, Magdalena (Department of Clinical Laboratory Sciences, 2021)
Background: We characterized B-cell non-Hodgkin lymphoma (NHL) cases over ten years at a tertiary children's hospital to contribute to the body of knowledge on pediatric lymphoma in developing countries with a high human immunodeficiency virus (HIV) burden. Methods: A retrospective cohort study using clinical and laboratory records of children newly diagnosed with B-cell NHL from January 2005 to December 2014. Results: Seventy-five children ≤ 15 years were included. The majority had Burkitt lymphoma (n = 61). Twenty-five percent (n = 19) were HIV positive and 16% (n = 12) had concurrent active tuberculosis. Bulky disease was present in 65.7% (n = 46) and 30.1% (n = 22) were classified as Lymphomes Malins B (LMB) risk group C. The five year survival estimates for HIV-negative and HIV-positive children were similar in our cohort: 81% vs. 79% for eventfree survival and 85% vs. 83.9% for overall survival. Of three children with Burkitt lymphoma, HIV and LMB group C, two died within one year. Conclusions: Irrespective of HIV status, the survival of children in our B-cell NHL cohort compares favorably with cure rates in developed nations, although advanced disease remains associated with a poor prognosis. Characterization of childhood NHL cases contributes to accurate risk stratification and tailored treatment.